1989
DOI: 10.1177/000456328902600303
|View full text |Cite
|
Sign up to set email alerts
|

18-Hydroxycorticosterone as a Marker for Primary Hyperaldosteronism

Abstract: An assay for the measurement of 18-hydroxycorticosterone (18-OHB) in plasma has been validated. The method involves extraction of plasma with dichloromethane, thin layer chromatography and radioimmunoassay with an iodinated 18-hydroxycorticosterone-3-carboxymethyloxime ligand. The plasma concentration of 18-OHB was measured in 16 patients with primary hyperaldosteronism and 20 control subjects. After overnight recumbency a significantly higher mean concentration of 18-OHB was found in the samples taken from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…This suggested that this corticosteroid may be used to diagnose the etiology of primary aldosteronism (9,19), but this view was not supported by others (20). This suggested that this corticosteroid may be used to diagnose the etiology of primary aldosteronism (9,19), but this view was not supported by others (20).…”
Section: Discussionmentioning
confidence: 95%
“…This suggested that this corticosteroid may be used to diagnose the etiology of primary aldosteronism (9,19), but this view was not supported by others (20). This suggested that this corticosteroid may be used to diagnose the etiology of primary aldosteronism (9,19), but this view was not supported by others (20).…”
Section: Discussionmentioning
confidence: 95%
“…Biglieri und Schambelan (14) fanden bei 23 Patienten mit primärem Hyperaldosteronismus (bei 5 infolge eines Nebennierenrinden-Adenoms), daß die Bestimmung des Plasma-18-OH-Corticosterons scharf zwischen den Patientengruppen trennen kann. Diese Ergebnisse konnten von anderen Autoren (auch bei Plasma-Bestimmung) nicht bestätigt werden (1,23). Unsere Auswertung an einem repräsentativen Patientenkollektiv läßt erkennen, daß einerseits in 7% der Adenom-Fälle Normalwerte und andererseits bei 17,3% der Hyperplasie-Fälle leicht bis mäßig erhöhte 18-OH-Corticosteron-Werte gefunden werden können.…”
Section: Tab 3b: Varianzanalyse Zur Ermittlung Der Trenneigenschafteunclassified
“…Auch andere Autoren fanden in kleineren Kollektiven bzw. vereinzelten Beobachtungen vergleichbare Ergebnisse (1,23). Eine normale 18-OH-Corticosteron-Ausscheidung bei Patienten mit Nebennierenrinden-Adenom kann Ausdruck einer veränderten Metabolisierung sein, derart, daß genügend Enzyme vorhanden sein müssen, die 18-OH-Corticosteron in Aldpsteron umwandeln, oder aber, daß Adenome zum Teil auch über alternative Biosynthesewege Aldosteron bilden können unter Umgehung von 18-OH-Corticosteron (24).…”
Section: Tab 3b: Varianzanalyse Zur Ermittlung Der Trenneigenschafteunclassified
“…As a result, the need for reliable biochemical indicators is urgent. Several endogenous biomarkers had been studied to reduce AVS, including urinary 18‐hydroxycortisol (18‐OHF) 9–13 . 18‐OHF is a hybrid steroid produced by the adrenal gland, which was discovered in the urine of a PA patient in 1982 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Several endogenous biomarkers had been studied to reduce AVS, including urinary 18‐hydroxycortisol (18‐OHF). 9 , 10 , 11 , 12 , 13 18‐OHF is a hybrid steroid produced by the adrenal gland, which was discovered in the urine of a PA patient in 1982. 14 Urinary 18‐OHF is low in healthy subjects, essential hypertensives, and PA patients with IHA but significantly increased in PA patients with APA and familial hyperaldosteronism.…”
Section: Introductionmentioning
confidence: 99%